Presymptomatic white matter integrity loss in familial frontotemporal dementia in the GENFI cohort: A cross‐sectional diffusion tensor imaging study. Issue 9 (11th July 2018) - Jiskoot, Lize C.; Bocchetta, Martina; Nicholas, Jennifer M.; Cash, David M.; Thomas, David; Modat, Marc; Ourselin, Sebastien; Rombouts, Serge A.R.B.; Dopper, Elise G.P.; Meeter, Lieke H.; Panman, Jessica L.; van Minkelen, Rick; et al.
Abstract: Objective: We aimed to investigate mutation‐specific white matter (WM) integrity changes in presymptomatic and symptomatic mutation carriers of the C9orf72, MAPT, and GRN mutations by use of diffusion‐weighted imaging within the Genetic Frontotemporal dementia Initiative (GENFI) study. Methods: One hundred and forty mutation carriers (54 C9orf72, 30 MAPT, 56 GRN ), 104 presymptomatic and 36 symptomatic, and 115 noncarriers underwent 3T diffusion tensor imaging. Linear mixed effects models were used to examine the association between diffusion parameters and years from estimated symptom onset in C9orf72, MAPT, and GRN mutation carriers versus noncarriers. Post hoc analyses were performed on presymptomatic mutation carriers only, as well as left–right asymmetry analyses on GRN mutation carriers versus noncarriers. Results: Diffusion changes in C9orf72 mutation carriers are present significantly earlier than both MAPT and GRN mutation carriers – characteristically in the posterior thalamic radiation and more posteriorly located tracts (e.g., splenium of the corpus callosum, posterior corona radiata), as early as 30 years before estimated symptom onset. MAPT mutation carriers showed early involvement of the uncinate fasciculus and cingulum, sparing the internal capsule, whereas involvement of the anterior and posterior internal capsule was found in GRN . Restricting analyses to presymptomatic mutation carriers only, similar – albeit less extensive – patterns were found: posteriorly located WM tracts (e.g., posterior thalamic radiation, splenium of the corpus callosum, posterior corona radiata) in presymptomatic C9orf72, the uncinate fasciculus in presymptomatic MAPT, and the internal capsule (anterior and posterior limbs) in presymptomatic GRN mutation carriers. In GRN, most tracts showed significant left–right differences in one or more diffusion parameter, with the most consistent results being found in the UF, EC, RPIC, and ALIC. Interpretation: This study demonstrates the presence of early and widespread WM integrity loss in presymptomatic FTD, and suggests a clear genotypic "fingerprint." Our findings corroborate the notion of FTD as a network‐based disease, where changes in connectivity are some of the earliest detectable features, and identify diffusion tensor imaging as a potential neuroimaging biomarker for disease‐tracking and ‐staging in presymptomatic to early‐stage familial FTD.